2011
DOI: 10.3174/ajnr.a2944
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of C-Arm CT Cerebral Blood Volume in a Canine Model of Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE:Previous studies have shown the feasibility of assessing qualitative CBV measurements in the angiography suite by using FPD-CBCT systems. We have investigated the correlation of FPD-CBCT CBV lesion volumes to the infarct volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…In addition, the fate of perforating arteries and optimization of the device to spare these small vessels must be incorporated into the modeling. Perhaps device miniaturization will soon be possible and allow for studying this technology in more relevant stroke models 21 that account for the complexity of brain reperfusion and permit assessment of functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fate of perforating arteries and optimization of the device to spare these small vessels must be incorporated into the modeling. Perhaps device miniaturization will soon be possible and allow for studying this technology in more relevant stroke models 21 that account for the complexity of brain reperfusion and permit assessment of functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Previous work has demonstrated qualitative and quantitative accuracy of CBV measurements made with the use of C-arm CT in conjunction with a contrast injection protocol aimed at delivering a steady-state of contrast in the parenchyma. [2][3][4][5][9][10][11] Although this method provides information that is helpful in better understanding the viability of ischemic tissue (ie, identifying tissue when autoregulation appears to be intact), it does not provide the ability to distinguish ischemic core from penumbra. Ganguly et al 8 and others 12,13 have recently demonstrated, in a swine model, the feasibility of the use of C-arm CT for dynamic perfusion measurement.…”
mentioning
confidence: 99%
“…Согласно результатам наблюдений, авторы обнаружи-ли, что CBV, по данным FP-CBCT, позволяет оценить изменения гемодинамики непосредственно до и после эндоваскулярного лечения. Кроме того, количествен-ный анализ объема зоны необратимого поражения, согласно данным FP-CBCT в моделях на животных, показал, что этот объем коррелировал с гистологичес-кими данными, но необходимо улучшить отношение сигнал/шум на изображении [27].…”
Section: церебральные артериовенозные мальформацииunclassified
“…In addition, a quantitative analysis of absolute lesion volumes determined from FP-CBCT-based cerebral blood volume in an animal model showed that lesion volumes correlated with histology but that improvement in terms of image signal-to-noise is required. 27 Although cerebral blood volume is believed to be a valuable parameter for brain infarction, cerebral blood flow is generally thought to offer improved discrimination between lesion and salvageable tissue. Assessment of cerebral blood flow using FP-CBCT is not a trivial task, because its acquisition time generally exceeds the time resolution needed to sample cerebral blood flow.…”
Section: Imagingmentioning
confidence: 99%